Short and Long Term Mortality Predictors in Octogenarians with Acute Coronary Syndromes - ÖZBEN SADIÇ, BESTE; ATAŞ, HALİL; TİGEN, MUSTAFA KÜRŞAT (My University, 2018)
Purpose: Octogenarians with acute coronary syndromes have higher mortality and morbidity due to higher prevalence of comorbidities and frailty. The aim of this study was to explore the predictors of short and long term mortality in octogenarians with ACS. Methods: Ninety-eight consecutive octogenarians presenting with acute coronary syndrome (mean age:84±3 years, 56 male) were included. All patients underwent coronary angiography and were given optimal medical treatment. The primary end point was cardiovascular mortality in hospital and at one year. Results: Fifteen patients died during hospitalization and 20 patients died after discharge within the first year. ST-segment-elevation myocardial infarction and hypotension were significantly more prevalent in the in-hospital mortality group while atrial fibrillation and hyponatremia were more prevalent in the long-term mortality group. All deceased patients had significantly lower left ventricular ejection fraction and glomerular filtration rate. Cox analysis revealed ST-segment-elevation myocardial infarction, hypotension and left ventricular ejection fraction as independent predictors of in-hospital mortality while hyponatremia, atrial fibrillation and renal dysfunction as independent predictors of long term mortality. Conclusion: It would be reasonable to pay further attention to octogenarians with acute coronary syndrome if they are presenting with ST-segment-elevation myocardial infarction, and have hypotension, impaired left ventricular function, hyponatremia, atrial fibrillation or renal dysfunction, which are associated with increased mortality.